Additive Manufacturing of a Cold‐Work Tool Steel using Electron Beam Melting. Issue 5 (26th November 2019) - Botero, Carlos; Ramsperger, Markus; Selte, Aydin; Åsvik, Kenneth; Koptyug, Andrey; Skoglund, Per; Roos, Stefan; Rännar, Lars-Erik; Bäckström, Mikael
Abstract : Metal additive manufacturing (AM) is on its way to industrialization. One of the most promising techniques within this field, electron beam melting (EBM), is nowadays used mostly for the fabrication of high‐performance Ti‐based alloy components for the aerospace and medical industry. Among the industrial applications envisioned for the future of EBM, the fabrication of high carbon steels for the tooling industry is of great interest. In this context, the process windows for dense and crack‐free specimens for a highly alloyed (Cr–Mo–V) cold‐work steel powder are presented in this article. High‐solidification rates during EBM processing lead to very fine and homogeneous microstructures. The influence of process parameters on the resulting microstructure and the chemical composition is investigated. In addition, preliminary results show very promising mechanical properties regarding the as‐built and heat‐treated microstructure of the obtained material. Abstract : The process windows for dense and crack‐free specimens for a highly alloyed (Cr–Mo–V) cold‐work steel powder, manufactured by electron beam melting (EBM), are investigated. High‐solidification rates during EBM processing lead to very fine and homogeneous microstructures, and preliminary results show very promising mechanical properties regarding the as‐built and heat‐treated microstructure of the obtained material.